2018
DOI: 10.1111/imj.13727
|View full text |Cite
|
Sign up to set email alerts
|

Results of a 10‐year follow‐up study of botulinum toxin A therapy for primary axillary hyperhidrosis in Australia

Abstract: Primary hyperhidrosis has a prevalence of 3-5% in the United States. It is a psychosocially disabling condition leading to low self-esteem, chronic stress and depressive symptoms. Several medical and surgical treatments exist, including botulinum toxin A, which internationally, has been shown effectively and safely to treat this condition achieving high patient satisfaction. In Australia, botulinum toxin A has been available under the Medicare benefits scheme for axillary hyperhidrosis since 2013, but efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
1
17
0
2
Order By: Relevance
“…The mean follow-up in our study was 5.5 years vs.2.73 years in our previous study, with a duration of data collection of 11 years (10). Another study in Australia lasted 10 years (9). The duration of our study allowed us to confirm the effectiveness of this treatment over a very long period.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The mean follow-up in our study was 5.5 years vs.2.73 years in our previous study, with a duration of data collection of 11 years (10). Another study in Australia lasted 10 years (9). The duration of our study allowed us to confirm the effectiveness of this treatment over a very long period.…”
Section: Discussionmentioning
confidence: 49%
“…BTA is a neurotoxin that is produced by the bacterium Clostridium botulinum. Treatment with BTA injections works by irreversibly blocking the release of the neuro transmitter acetylcholine from presynaptic bulbs at the neuromuscular junction (9). This leads to degeneration of the nerve endings, which can redevelop in a few weeks.…”
Section: Changes In the Duration Of Efficacy Of Botulinum Toxin A Injmentioning
confidence: 99%
“…The unique characteristics of the hidden blade scalpel are determined by its shape; it can scrape the underside of the gland and can reach the level of the hair follicles emerging from the subdermal layer, allowing for complete removal of all sweat glands, apocrine glands, and hair follicles. This result is confirmed by the histological appearance and is not achieved or is lessened using nonsurgical approaches, such as injection of botulinum toxin A 10 -12 and ultrasonic aspiration. 13 -15 Patients return to their normal lives quickly and are satisfied with the success and appearance of their surgical treatment.…”
Section: Discussionmentioning
confidence: 84%
“…Chronic migraine with and without medication overuse (A) [2][3][4][5] Blepharospasm (A) 5,25 Spasmodic dysphonia (A) 10 Cervical dystonia (A) 5,16 Limb spasticity (A) 31 Primary axillary hyperhidrosis (A) 11,12 Overactive bladder, idiopathic overactive bladder, and neurogenic bladder (A) 28…”
Section: Beneficialmentioning
confidence: 99%
“…11 A 10-year retrospective study in patients ages 12 years and older showed a 75% to 100% improvement in hyperhidrosis, with a median treatment effect duration of 7 months. 12 ❚ Sialorrhea, or hypersalivation, is typically associated with neurological conditions such as cerebral palsy, amyotrophic lateral sclerosis, Parkinson disease, and posttraumatic brain injuries. It typically is treated with anticholinergic drugs, surgery, and irradiation of salivary glands, which can have significant adverse effects and complications.…”
Section: Ent Disordersmentioning
confidence: 99%